2009
DOI: 10.1038/ni.1740
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II–dependent basophil–CD4+ T cell interactions promote TH2 cytokine–dependent immunity

Abstract: Dendritic cells can prime naïve CD4+ T cells, however we demonstrate that DC-mediated priming is insufficient for the development of TH2 cell-dependent immunity. We identify basophils as a dominant cell population that coexpressed MHC class II and Il4 message following helminth infection. Basophilia was promoted by thymic stromal lymphopoietin (TSLP) and depletion of basophils impaired immunity to helminth infection. In vitro, basophils promoted antigen-specific CD4+ T cell proliferation and IL-4 production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
611
7
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 548 publications
(657 citation statements)
references
References 58 publications
30
611
7
9
Order By: Relevance
“…We next sought to assess which cell populations are critical for antigen presentation in our model. We first showed that basophils (17)(18)(19)(20)(21)(22) are not required for Nod-driven Th2 differentiation (Fig. S2).…”
Section: Ligand Sensing In the Stromal Compartment Is Necessary Formentioning
confidence: 99%
“…We next sought to assess which cell populations are critical for antigen presentation in our model. We first showed that basophils (17)(18)(19)(20)(21)(22) are not required for Nod-driven Th2 differentiation (Fig. S2).…”
Section: Ligand Sensing In the Stromal Compartment Is Necessary Formentioning
confidence: 99%
“…Thus, even though the findings presented herein are based on a small dataset of heterogeneous tumor subtypes, and our results may be biased because of sample selection favoring large and/or less CTX-responsive tumors among the CTX-treated group, the clear distinctions in the myeloid profiles between CTX-naive and CTX-treated tumors is provocative and indicates that a CSF1-targeted strategy may be a promising approach to enhance therapeutic efficacy of cytotoxic CTX, particularly for treatment of refractory BC. Moreover, given the increase in granulocytic populations within tumors resistant to CTX, and the involvement of these cells in regulating immune responses in chronic inflammatory diseases (58)(59)(60)(61)(62), these populations may also be functionally relevant, and targeting common pathways of immune suppression within the tumor microenvironment may provide additional therapeutic opportunities to increase efficacy of neoadjuvant CTX. …”
Section: Discussionmentioning
confidence: 99%
“…127 For instance, dendritic cells in the skin of mice that are exposed to N. brasiliensis larvae or the contact sensitizer dibutyl phthalate (both of which induce type 2 immunity) acquire distinct transcriptional profiles, revealing a previously unappreciated role for type I interferons during parasite infection, 128 and highlighting the complicated nature of pathogen recognition by the innate immune system. Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue.…”
Section: Inductionmentioning
confidence: 99%